The Effect of Perlite Content on the Combustion Resistance of Wood Plastic Composites - Özdemir, Ferhat (Bartın Üniversitesi, 2020)
In this study, the effects of perlite use on fire resistance in wood plastic composite production were investigated. Scots pine wood flour, polypropylene and perlite using certain proportions of wood plastic composite materials were produced by flat-presses method. In the production of wood plastic composites, 5%, 10%, 15% and 20% perlite was used in the mixture. Test samples were obtained from the produced wood plastic composite boards in accordance with the relevant standards. Horizontal and vertical combustion rate and Limited Oxygen Index tests were performed to determine the fire resistance properties. Horizontal combustion rate (ASTM D 635), vertical combustion rate (UL-94) and LOI test (ASTM 2863-09 standards) were carried out. As a result, according to both the horizontal-vertical combustion rate and LOI data, It has been determined that perlite improves the fire resistance due to the increase in the usage rate. In the production of wood plastic composite, the most positive effect on fire resistance was determined at a 20% perlite usage rate. It was concluded that this effect increased with the use of MAPP.

Bu çalışmada odun plastik kompozit üretiminde perlit kullanımının yanma dayanımı üzerine etkileri araştırılmıştır. Sarıçam odun unu, polipropilen ve perlit belirli oranlarda kullanılarak odun plastik kompozit malzemeler doğrudan pres yöntemi ile üretilmiştir. Üretilen odun plastik kompozitlerin üretiminde karışımın %5, %10, %15 ve %20 oranlarında perlit kullanılmıştır. Üretilen odun plastik kompozit levhalardan ilgili standartlara uygun olarak test numuneleri elde edilmiştir. Yanma dayanım özelliklerinin belirlenmesinde yatay ve dikey yanma hızı ve Limited Oksijen Index testleri yapılmıştır. Yatay yanma hızı ASTM D 635, dikey yanma hızı (UL 94) ve LOI testi ASTM 2863-09 standartlarına uygun olarak yapılmıştır. Sonuçta hem yatay ve dikey yanma hızı hem de LOI ile ilgili verilere göre perlit kullanım oranının artmasına bağlı olarak yanma dayanımını iyileştirdiği belirlenmiştir. Odun plastik malzeme üretiminde yanma dayanımı için en olumlu etki %20 perlit kullanım oranında tespit edilmiştir. MAPP kullanımı ile bu etkinin arttığı sonucuna ulaşılmıştır.
Perlit İçeriğinin Odun Plastik Kompozitlerin Yanma Dayanımına Etkisi
2018/1-8
Keywords: Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler